Synthesis, characterization and thermal behaviour of solid-state compounds of europium(III) and gadolinium(III) 3-methoxybenzoate - Dametto, Patricia R. [UNESP]; Ambrozini, Beatriz [UNESP]; Siqueira, Adriano B. [UNESP]; Carvalho, Claudio T. [UNESP]; Ionashiro, Massao [UNESP] (Springer, 2009)
Solid-state Ln-C(8)H(7)O(3) compounds, where Ln stands for Eu(III) and Gd(III) and C(8)H(7)O(3) is 3-methoxybenzoate, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy, elemental analysis and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to information about the composition, dehydration, thermal stability and decomposition of the isolated compounds.
Keywords: Eu(III); Gd(III); 3-Methoxybenzoate; Thermal behaviour